Driving mechanism for farmers to adopt improved agricultural systems in China: The case of rice-green manure crops rotation system. (August 2021) - Li, Fuduo; Zhang, Kangjie; Ren, Jing; Yin, Changbin; Zhang, Yang; Nie, Jun
Abstract: CONTEXT: Farmers' decision-making related to the use of winter fallow fields is an issue of great concern to policymakers in China. An improved agricultural system, the rice-green manure rotation system (RGRS), has attracted more and more attention because of its efficient utilization of these fields and its outstanding comprehensive benefits. Despite the government's growing promotion, unfortunately low adoption has been observed among farmers. OBJECTIVE: In this case, exploring the factors that affect farmers' adoption of RGRS has become the key to crack the above dilemma. METHODS: This study therefore aims to reveal the factors determining farmers' intention and behavior to adopt RGRS by extending the theory of planned behavior (TPB) based on 1217 samples collected in the southern paddy field region (SPR) of China. RESULTS AND CONCLUSIONS: Results firstly validated the applicability of the extended TPB framework in analyzing farmers' intention and behavior to adopt RGRS. Subsequently, we found that farmers' intention to adopt RGRS can be greatly influenced by the perceived behavioral control, especially the control beliefs with regard to capital restriction and the expected environmental benefits of RGRS. Therefore, supportive policies should be formulated to improve farmers' behavioral capacity and, specialized training should be organized to improve their expected environmental benefits. Subjective norm, especially those derived from interpersonal relationships, emerged as another pivotal independent predictor of farmers' intention to adopt RGRS. This observation provides policy makers with enlightenment that strengthening the interpersonal social network is highly valued to improve farmers' adoption intention. Another finding is that there was a highly positive consistency between farmers' intention and behavior to adopt RGRS, which provides a possibility to predict, strengthen and test farmers' behavior based on their intention. More importantly, the comparison between the estimation results of the extended model and the original model shows that eco-compensation significantly increased the probability of intention being converted into behavior by moderating the influence intensity of perceived behavioral control on intention. SIGNIFICANCE: These results can help policy makers better understand which influence farmers' adoption of RGRS and what targeted measures can be taken to popularize the improved agricultural system. Graphical abstract: Unlabelled Image Highlights: The theory of planned behavior was extended to analyze farmers' adoption of RGRS. Perceived behavioral control had the greatest impact on farmers' intention. A positive consistency existed between farmers' intention and behavior. Eco-compensation increased the probability of farmers' intention being converted into behavior.